Analisis Strategi Pemasaran Hotel Sotis Kupang dalam Menghadapi Tantangan pasca Pandemi Covid-19 - Oematan, Esti Cristind Natalia (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
The Corona virus pandemic which caused commotion around the city has had a significant impact on the Indonesian hospitality sector. The Covid-19 pandemic in Indonesia has become a disaster for the hotel industry due to media reports about the closure of the hotel industry. Hoteliers, tourism entrepreneurs, hotel associations and the government have carried out various strategies to reduce the impact of losses on the hospitality industry, especially in Indonesia. This study aims to determine the optimal marketing strategy for SOTIS Hotel Kupang after the Covid 19 pandemic. Observation, interviews, and qualitative descriptive methods were used in this study and data collection from the library, interpretation and description of data and existing data. This study shows that SOTIS Hotel Kupang uses an evaluation system to create and innovate after the corona virus pandemic so that the business runs and generates economic value.